2020
DOI: 10.1007/s00221-020-05983-9
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid receptor activation ameliorates lipopolysaccharide-induced inflammation and apoptosis by inhibiting the MAPK/caspase-3 pathway in BV2 microglial cells

Abstract: Delta-opioid receptor (DOR) is widely distributed in the central nervous system, and its activation protects against ischaemic/hypoxic brain injury. However, the role of DOR in microglia in ischaemic stroke has not yet been fully investigated. We found that DOR was expressed in both human and mouse cerebral microglia, besides, it was upregulated in activated BV2 microglial cells by immunofluorescence staining and Western blot. DOR activation by the specific agonist TAN-67 significantly enhanced BV2 microglial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
(51 reference statements)
1
18
1
Order By: Relevance
“…We provided the first evidence in this work that DOR maintained a low density in the BV2 cells, and its expression was closely associated with microglial dynamic polarization. Our data partially support the view of Cheng et al (2021) , who found a colocalization of DOR protein and CD68 + or F4/80 + labeled microglia in human and mouse brain tissues as well as an existence of DOR in BV2 culture cells. However, there is a major difference between our findings and those of Cheng’s in terms of the regulation of DOR expression in LPS-treated BV2 cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We provided the first evidence in this work that DOR maintained a low density in the BV2 cells, and its expression was closely associated with microglial dynamic polarization. Our data partially support the view of Cheng et al (2021) , who found a colocalization of DOR protein and CD68 + or F4/80 + labeled microglia in human and mouse brain tissues as well as an existence of DOR in BV2 culture cells. However, there is a major difference between our findings and those of Cheng’s in terms of the regulation of DOR expression in LPS-treated BV2 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were based on the simultaneous comparison among LPS, IL4 and hypoxia groups and the consistency of both immunofluorescent and Western blot data. The reasons behind the difference between our observations and those of Cheng et al (2021) are very likely related to the differences in the concentrations of LPS and the exposure durations between our and their experiments because DOR expression is sensitive to various stresses and differs in different conditions ( Ma et al, 2005 ; Popiolek-Barczyk and Mika, 2016 ; Zhu et al, 2018 ; Polo et al, 2019 ; Xu et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Those cells constantly survey the brain milieu and in response to altered microenvironment homeostasis, microglia cells become reactive and can shift their morphology, which facilitates migration to the injury site ( Thameem Dheen et al, 2007 ; Griffiths et al, 2009 ). Marked and disseminated microglial reaction may result and perpetuate the neuroinflammatory state, also contributing to the neurodegeneration through the release of free radicals, excessive nitric oxide (NO), inducible nitric oxide synthase (iNOS), and multiple chemokines and cytokines, such as IL-1β, IL-6, IL-8, IL-12, IL-15, IL-10, and TNF-α ( Shinozaki et al, 2019 ; Cheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%